2015
DOI: 10.25055/jksrnt.2015.6.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Tobacco Use Disorders in People with Mental Illness

Abstract: People with mental illness have higher smoking prevalence, and less success in stopping smoking compared with the general population. Furthermore, smoking-related medical illness may be the leading cause of death in smokers with mental illness. Though smokers with mental illness have been excluded from most of large clinical trials for tobacco use disorder, there is a growing evidence to guide clinicians in assisting their patients with mental illness to quit smoking. The objective of this review is to summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Pharmacotherapy combined with behavioral treatment was effective for patients with mental disorders 41). A variety of systematic strategies should be developed to help patients with psychosis quit smoking 42)…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacotherapy combined with behavioral treatment was effective for patients with mental disorders 41). A variety of systematic strategies should be developed to help patients with psychosis quit smoking 42)…”
Section: Discussionmentioning
confidence: 99%
“…While the results of the present study pertaining to nicotine dependence were not significant, a previous study reported that people with disabilities with high nicotine dependence are at risk of consuming multiple cigarettes and may face challenges when quitting smoking [23], indicating the need for further research. Specifically, people with mental health disorders showed an extremely high smoking rate and nicotine dependence [26]; thus, providing customized, varied, and aggressive smoking cessation services according to disability type could markedly reduce the smoking rate among people with disabilities.…”
Section: Discussionmentioning
confidence: 99%